identité du mois de juillet 2015

Posté le : jeudi 2 juillet 2015 par Vincent Thill
A=4a(a-3b)(2a^2+ab+3b^2)(5a^2+6ab+9b^2)(3a^2-2ab+3b^2) B=2(a+b)(a+3b)(7a^2+9b^2)(a^2+3b^2)(13a^2+6ab+9b^2) X=(a+b)(a+3b)(7a^2+9b^2)(3a^2-2ab+3b^2)(5a^2+6ab+9b^2) Y=8a(a-3b)(a^2+3b^2)(2a^2+ab+3b^2)(13a^2+6ab+9b^2)

avec        A² + B² = C²    et    X² + Y² = Z²        ainsi que    ( A )( B ) = ( X )( Y )

on a l’équation    A^4+B^4+Z^4 = X^4+Y^4+C^4

exemple    a = 2    et    b = 3

(-8492904)^4+(62815610)^4+(32718737)^4 =

(22175505)^4+(24057488)^4+(63387146)^4.

Tags:

Les commentaires sont fermés